Effects of formulation and operating variables on Zanamivir dry powder inhalation characteristics and aerosolization performance. (September 2014) - Yang, Yang; Yang, Ziwei; Ren, Yufeng; Mei, Xingguo
Abstract The objective of this study was to investigate the influence of formulation and operating variables on the physical characteristics and aerosolization performance of zanamivir spary-dried powders for inhalation. Spray-dried samples of zanamivir, zanamivir/mannitol and zanamivir/mannitol/leucine were prepared from their corresponding aqueous solutions under the same conditions to study the influence of the composition, and zanamivir/mannitol/leucine (1/1/3 by weight) formulation was used for investigation of the effect of the preparation process. Dry powders were characterized afterwards for different physical properties, including morphology, particle size, flowability, density and moisture absorption. The in vitro deposition was also evaluated after the aerosolization of powders at 100 L min−1 via the Aerolizer® into a Next Generation Impactor (NGI). The highest FPF of 41.40 ± 1.1% was obtained with a zanamivir/mannitol/leucine ratio of 1/1/3, which had an average Dg of 3.11 ± 0.13 μm and an angle of repose of 36° ± 1. It was found that the influence of the preparation process on zanamivir spary-dried powders characteristics and aerosolization properties was relatively small, but the influence of the composition was relatively large. Optimization of DPI can be achieved by selecting the most appropriate formulation and preparation process.